Criteria for assessing children's abilities when selecting them for hockey - Udalova, M.A.; Morozova, L.V.; Kiryanova, L.A.; Lyashenko, O.V. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to identify technical movements with the ball that carry a high risk of losing the object. To develop and justify the effectiveness of ball exercises in group rhythmic gymnastics exercises. Methods and structure of the study. Analysis of literature, video material of competitive programmes of group gymnasts, pedagogical observation of the training process, pedagogical testing of technical preparedness with a ball, mathematical and statistical data processing. The study involved gymnasts performing group exercises as part of the candidate master of sports and master of sports programmes (n=20). Results and conclusions. As a result of the conducted research, structural groups of movements with the ball have been identified, the performance of which is associated with a high risk of object loss. The causes of errors in these structural groups are analyzed. Exercises have been developed aimed at improving the reliability of individual components of subject training with a ball in group exercises of rhythmic gymnastics.